Kemampuan Guru dalam Pembelajaran Baca Tulis Permulaan di Sekolah Dasar - Alif Mudiono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Teachers' Competence in Early-Literacy Learning. The study aimed at describing objectively teachers' competence in developing early literacy at elementary schools. Descriptive-qualitative analysis was employed to analyze the data which had been collected from first-grade teachers of three elementary schools in Blitar using Teacher-Competence Evaluation Instrument, documentation study, and field notes. The results suggest that teachers' competence in early-literacy learning, which involves planning, implementing, and evaluating, has not yet met the requirements of the 1994 curriculum of elementary school.